Opening the Black Box - Jessica M. Eaglin (Washington University Journal of Law and Policy, 2025)
In response to the tenth anniversary of the Ferguson uprisings, this Essay examines how the protests reshaped legal discourse on algorithmic decision-making in criminal law, with a specific focus on systemic racial injustice. By deconstructing the metaphorical “black box,” the Essay surveys the intersection of race, technology, and incarceration while also illustrating how the uprisings influenced public and scholarly engagement with criminal legal technologies. The Essay analyzes current critiques and cautions against focusing too narrowly on reforming specific technologies rather than addressing the legal and social structures that sustain racial inequality. The Essay concludes by urging scholars and policymakers to engage with the structural dimensions of technology in criminal law and develop more comprehensive approaches to justice in the digital age.
Keywords: FergusonToAlgorithm; TechAndJustice; DigitalRacialEquity